Musculoskeletal demands of progressions for the longswing on high bar - Irwin, G.; Kerwin, D. G. (Sports Biomechanics, 2007)
Kinetic analyses of the chalked bar longswing on high bar and its associated progressions were used to explain musculoskeletal contributions during the performance of these skills. Data on four international male gymnasts performing three series of chalked bar longswings and eight progressions were recorded. Customized body segment inertia parameters, two-dimensional kinematics (50 Hz), and bar forces (1000 Hz) were used as input to inverse dynamic modelling. The analysis focused on the relative contributions of the knees, hips, and shoulders with root mean squared differences between the chalked bar longswing and the progressions being used to rank the progressions. Seventy per cent of the total work occurred between 200° and 240° of angular rotation in the longswing, 67% of which was contributed by the shoulders. The shoulders were also dominant in all progressions, with the largest such contribution occurring in the looped bar longswing with "no action". The least similar progression was the looped bar pendulum swing, while the most similar was the chalked bar bent knee longswing. This study provides a useful means for ranking progressions based on their kinetic similarity to the chalked bar longswing and builds on earlier research in identifying that progressions can be classified into those similar in physical demand (kinetics) and those similar in geometry (kinematics).